Muslim Communal Politics and Partition of India: Exploring the Factors behind Muslim Communal Politics and the Partition of India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Imperialist and Cambridge historiography on theMuslim Communal politics and partition of India and on the political changesamong the Muslims of colonial India tend to fall into five separatecategories.  The historians of the firstcategory are of the opinion that the omissions, tactical errors and diplomaticblunders on the part of the Indian National Congress changed the Muslimpolitics and led to the growth of the Muslim Communal politics subsequentlyresulting in the form of the partition of India. The second category of thesehistorians are of the opinion that the forces of the colonial policy and theconstitutional measures adopted by the colonial state helped to the emergenceand growth of the Muslim communal politics and led to the partition ofIndia.  It has been suggested by the  third category  of  these scholars  that  the growth  of  the Muslim  separatism  in India  was manipulated  and determined  by  the Muslim  elites  at the  national  and provincial  level  whose propaganda based on communalidentification was responded to the Muslims of colonial India. The historiansof the fourth category have argued that although the colonial policy and itsevolution of the representative from  of  the government  led  to the  emergence  and consolidation  of  the Muslim communal politics but the demand of a separate Muslim state wasnot the design of Muslims of India. It has been viewed by the scholars of thefifth category that the Muslim separatism in colonial India and the partitionof India was the result of the interplay between the three major political playersi.e., the British, the Indian National Congress and the All India Muslim Leagueand that the partition of India was a first major act of decolonization.